Repolarization reserve, arrhythmia and new drug development - Yang Li; Yicheng Fu (Elsevier, 2013)
Repolarization-related lethal arrhythmias have led to the concept of "repolarization reserve", which may help elucidate the relationship between K+ currents and other components of repolarization. Pharmacological manipulation as well as congenital and cardiac disease may affect repolarization and alter the repolarization reserve, leading to the development of arrhythmias. Pharmacological enhancement of outward currents or suppression of inward currents has been shown to be of therapeutic value. A number of newly found selective ion channel inhibitors or agonists have been investigated for their ability to enhance repolarization reserve and decrease the incidence of arrhythmia. In this paper we review the development, potential mechanisms, clinical application, and pharmacological significance of repolarization reserve in order to better understand, predict and prevent unexplained adverse cardiac events.